Stratifikasi Sosial Pada Tradisi Kawin Bangsawan Menak Masyarakat Lombok Timur - Alfiyah Faizatul Arif (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2022)
The East Lombok sasak tribal community group has a customary marriage rule that requires a noble woman menak to marry a man of the same lineage and prohibits marrying non-nobles under the pretext of incompatibility. This research was conducted to examine the practice of marriage of menak nobles based on the same social stratification. This research is a qualitative type with library research. The approach used is legal sociology which explains a law at a practical and empirical level in the people of East Lombok. Meanwhile, this data collection method is by observation method in books and other references relevant to this research. It can be concluded that the marriage tradition of menak nobles in East Lombok was influenced by the existence of a social stratification system from past civilizations when they still adhered to the employment system, thus giving birth to a rule prohibiting marriage with non-noble menak men under the pretext of not matching.